Screening for dual-target enzyme inhibitors derived from Gardenia jasminoides roots, a medicinal and edible plant: investigation of their potential anti-dementia activity - Liu, Xuanlin; Zhou, Yang; Meng, Rui; Han, Jingyi; Chen, Ming; Bo, Xiangjie; Li, Sainan; Song, Daqian; Zhang, Yuchi (Frontiers in Nutrition, 2025)
IntroductionGardenia jasminoides root (GJR) is a traditional Chinese plant valued for its dual functions as both a medicinal herb and an edible resource. Alzheimer's disease (AD) is an irreversible, fatal neurodegenerative disorder in the elderly, and current treatments mainly rely on single-target acetylcholinesterase (AChE) inhibitors with limited effects on disease progression. Thus, there is an urgent need to develop dual-target inhibitors that regulate inflammation (via 5-lipoxygenase, 5-LOX) and improve cholinergic dysfunction (via AChE).MethodsTo efficiently and accurately screen active compounds, receptor-ligand affinity ultrafiltration coupled with enzyme kinetics was used for rapid identification and characterization. Biochemical assays validated the inhibitory activities and mechanisms of the compounds, while molecular docking and molecular dynamics simulations evaluated target binding affinity and stability at the atomic level. An offline two-dimensional chromatographic method was developed to overcome the limitations of conventional countercurrent chromatography, enhancing peak capacity, and separation efficiency.ResultsSeven active compounds were successfully isolated and identified from GJR, including Shanziside, Deacetylasperulosidic acid methyl ester, Gardoside, Shanzhiside methyl ester, Mussaenoside acid, Eleutheroside E, and 5-Hydroxy-3′,4′-dimethoxyflavone. These compounds exhibit potential dual-target inhibitory effects on 5-LOX and AChE, laying the foundation for anti-AD research.DiscussionThis study integrates advanced screening, optimized extraction, and rigorous bioactivity assessment to elucidate the active components of GJR and their anti-AD potential. The developed methodology addresses the shortcomings of single-target drug development and provides valuable insights for the development of dual-target inhibitors and the advancement of plant-based food preparation technologies.